Exponential Concept Modeling for Rainfall Duration Forecasting at SMAN1 Sukapura - Agustin, Safrina Ayunindar Dwi; Jenis; Sugiono, Moch. (Mathematics Education Journal, 2025)
This study aims to predict rainfall duration using an exponential approach based on applied mathematics. Data were obtained from three rainfall events with different characteristics that were observed directly at SMAN 1 Sukapura. The research method used an applied observational quantitative study of a cross-sectional nature. The modeling results show that the decay constant value varies between rainfall events, reflecting differences in the rate of intensity decline after reaching its peak. The predicted time of rainfall cessation differed by 4–6 minutes from the field observations. Evaluation of the model's accuracy using Mean Absolute Percentage Error (MAPE) yielded values of 1.32%, 2.10%, and 3.64%, all of which were below the 10% threshold. These findings indicate that the exponential model is capable of quantitatively representing the decay pattern of rainfall intensity with excellent accuracy but has limitations in representing fluctuations in rainfall intensity.